2000
DOI: 10.1111/1467-9450.00191
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between locus of control, level of ability and gender

Abstract: In a sample of Norwegian 14- and 15-year-old students no significant relationship was found between total externality-internality score and level of ability. However, a significant relationship was found between ability and a subscale of locus of control related to degree of belief in the impact of school effort. The analyses of gender differences showed that girls had significantly higher total internal locus of control scores than boys. Boys were, however, significantly more internally oriented than girls on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
2
13
0
5
Order By: Relevance
“…As regards differences according to sex, men scored significantly higher in external locus of control, and women in internal locus of control (p> .05). These results confirm the findings of Manager and Eikeland (2000). The results related to the difference in terms of completed studies show that the scores in external LOC are higher for the lowest educational levels.…”
Section: Discussionsupporting
confidence: 90%
“…As regards differences according to sex, men scored significantly higher in external locus of control, and women in internal locus of control (p> .05). These results confirm the findings of Manager and Eikeland (2000). The results related to the difference in terms of completed studies show that the scores in external LOC are higher for the lowest educational levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, the difference in locus of control may have been affected by the composition of our sample. Although some researchers (Manger & Eikeland, 2000;Olvera, Remy, Power, Bellamy, & Hays, 2001) have suggested that males have a more external locus of control than do females, others have argued that females have a more external locus of control than do males (Cairns, McWhirter, Duffy, & Barry, 1990;Wehmeyer, 1993). However, a number of scholars have suggested that gender difference in locus of control is not significant (Cooper, Burger, & Good, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to gender differences in sport locus of control, some researchers have shown that women tend to demonstrate higher levels of internal orientation than do men (Manger & Eikeland, 2000;O'Brien, Smith, Bush, & Peleg, 1990;Olvera, Remy, Power, Bellamy, & Hays, 2001), yet others have reported the opposite finding (Cairns, McWhirter, Duffy, & Barry, 1990;Wehmeyer, 1993). Still other researchers have shown that locus of control does not differ across gender (Altman & Revenson, 1985;Cooper, Burger, & Good, 1981;Heretick, 1981;Parcel & Meyer, 1978).…”
Section: Discussionmentioning
confidence: 99%